Clinical practice guidelines for IgG4‐related sclerosing cholangitis. (18th January 2019) - Kamisawa, Terumi; Nakazawa, Takahiro; Tazuma, Susumu; Zen, Yoh; Tanaka, Atsushi; Ohara, Hirotaka; Muraki, Takashi; Inui, Kazuo; Inoue, Dai; Nishino, Takayoshi; Naitoh, Itaru; Itoi, Takao; et al.
Abstract: IgG4‐related sclerosing cholangitis (IgG4‐SC) is a distinct type of cholangitis frequently associated with autoimmune pancreatitis and currently recognized as a biliary manifestation of IgG4‐related disease. Although clinical diagnostic criteria of IgG4‐SC were established in 2012, differential diagnosis from primary sclerosing cholangitis and cholangiocarcinoma is sometimes difficult. Furthermore, no practical guidelines for IgG4‐SC are available. Because the evidence level of most articles retrieved through searching the PubMed, Cochrane Library, and Igaku Chuo Zasshi databases was below C based on the systematic review evaluation system of clinical practice guidelines MINDS 2014, we developed consensus guidelines using the modified Delphi approach. Three committees (a guideline creating committee, an expert panelist committee for rating statements according to the modified Delphi method, and an evaluating committee) were organized. Eighteen clinical questions (CQs) with clinical statements were developed regarding diagnosis (14 CQs) and treatment (4 CQs). Recommendation levels for clinical statements were set using the modified Delphi approach. The guidelines explain methods for accurate diagnosis, and safe and appropriate treatment of IgG4‐SC. Abstract : Highlight IgG4‐related sclerosing cholangitis is recognized as a biliary manifestation of IgG4‐related disease, and differential diagnosis from primary sclerosing cholangitis and cholangiocarcinoma is sometimes difficult. Kamisawa and colleagues developed consensus guidelines using the modified Delphi approach. The guidelines explain methods for accurate diagnosis, and safe and appropriate treatment of IgG4‐related sclerosing cholangitis.